2013
DOI: 10.1002/pssr.201307254
|View full text |Cite
|
Sign up to set email alerts
|

Micro gratings written in ZnO:Al thin films using picosecond UV‐laser interference patterning

Abstract: Diffraction micro gratings have been written in ZnO:Al thin films using a picosecond laser operating at 355 nm. Micro gratings of 20 µm diameter with a period of 860 nm show a groove depth up to 120 nm. The total transmittance of square‐centimeter‐size grating‐textured ZnO:Al films was almost unchanged after grating formation, while the sheet resistance increased moderately. The textured films reached haze values of 9% at 700 nm. This simple texturing method can be applied also to ZnO:Al films that cannot be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…At higher pulse energies, too much energy is deposited; the surface melts and no grooves are formed. In previous work [25] we showed that for the laser parameters used here, no loss of transmittance of the ZnO:Al film due to laser texturing can be observed. The optical scatter properties of the front contact samples have been characterized using haze and ARS measurements.…”
Section: Methodsmentioning
confidence: 71%
See 3 more Smart Citations
“…At higher pulse energies, too much energy is deposited; the surface melts and no grooves are formed. In previous work [25] we showed that for the laser parameters used here, no loss of transmittance of the ZnO:Al film due to laser texturing can be observed. The optical scatter properties of the front contact samples have been characterized using haze and ARS measurements.…”
Section: Methodsmentioning
confidence: 71%
“…The formation of the gratings by interfering pulsed laser beams has been discussed in the Refs. [24,25]. The grooves are deepest near the center of the micro grating where the local intensity of the interference modulated Gaussian intensity profile is strongest.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…There are also other groups working with textured glasses, but in combination with, e.g., boron‐doped ZnO grown by low‐pressure chemical vapor deposition 5 or conventionally thick, wet‐chemically texturized ZnO:Al 6. We want to note that there are also other concepts for introducing light trapping such as direct laser interference patterning (DLIP) 7. In contrast to recent reports where UV nano‐imprint lithography (UV‐NIL) is used to texturize a lacquer (containing organic components) on glass 8, 9, the use of textured glass (and the DLIP approach) is also compatible with high‐temperature processes.…”
Section: Introductionmentioning
confidence: 99%